Multiple Hits in Acute Pancreatitis: Components of Metabolic Syndrome Synergize Each Other’s Deteriorating Effects - Szentesi, Andrea; Párniczky, Andrea; Vincze, Áron; Bajor, Judit; Gódi, Szilárd; Sarlós, Patricia; Gede, Noémi; Izbéki, Ferenc; Halász, Adrienn; Márta, Katalin; Dobszai, Dalma; Török, Imola; et al. (Frontiers in Physiology, 2019)
Introduction: The incidence of acute pancreatitis (AP), and the prevalence of metabolic syndrome (MetS) are growing worldwide. Several studies confirmed that obesity (OB), hyperlipidemia (HL) or diabetes mellitus (DM) can increase the severity, mortality and complications in AP. However, there is no comprehensive information on the independent or joint effect of MetS components on the outcome of AP. Our aims were 1) to understand whether the components of MetS have an independent effect on the outcome of AP, and 2) to examine the joint effect of their combinations. Methods: From 2012 to 2017, 1435 AP cases from 28 centers were included in the prospective Acute Pancreatitis Registry. Patient groups were formed retrospectively based on the presence of OB, HL, DM and hypertension (HT). The primary endpoints were mortality, severity, complications of AP and length of hospital stay. Odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results: 1257 patients (55.7±17.0 years) were included in the analysis. The presence of OB was an independent predictive factor for renal failure (OR: 2.98, [CI: 1.33-6.66]) and obese patients spent longer time in hospital as compared to non-obese patients (12.1 vs. 10.4 days, p = 0.008). HT increased the risk of severe AP (OR: 3.41, [CI: 1.39-8.37]), renal failure (OR: 7.46, [CI: 1.61-34.49]) and the length of hospitalization (11.8 vs. 10.5 days, p = 0.020). HL increased the risk of local complications (OR: 1.51, [CI: 1.10-2.07), renal failure (OR: 6.4, [CI: 1.93-21.17]) and the incidence of newly diagnosed DM (OR: 2.55, [CI: 1.26-5.19]). No association was found between the presence of DM and the outcome of AP. 906 cases (mean age±SD: 56.9±16.7 years) had data of all 4 components of MetS available. The presence of two, three or four MetS factors increased the incidence of the unfavorable outcome as compared to patients with no MetS factors. Conclusions: OB, HT and HL are independent risk factors for several complications. HT is an independent risk factor for severity as well. Components of MetS strongly synergize each other’s detrimental effect. It is important to look for and follow-up on the components of MetS in AP.